Influence of pH-Responsive Monomer Content on the Behavior of Di-Block Copolymers in Solution and as Stabilizers of Pickering Latex Particle Emulsifiers - Manga, Mohamed S.; Cayre, Olivier J.; Biggs, Simon; Hunter, Timothy N. (Frontiers in Chemistry, 2018)
In this study, diblock copolymers poly(methyl methacrylate) - block - poly(2-dimethylaminoethyl methacrylate) (pMMA-b-pDMAEMA) are investigated for use in the steric stabilization of latex particles and the subsequent use of these latex particles as Pickering emulsifiers. Solution properties of the diblock copolymers highlight that the pDMAEMA block length influences the critical micelle concentration and micelle hydrodynamic diameter in response to changes in pH and the pKa. The block length can also be used as a way to control the particle size of sterically stabilized polystyrene latex particles prepared via emulsion polymerization. The solution properties of these latex particles are also presented. Emulsion studies using these latex particles as emulsifiers show that both solution pH and electrolyte concentrations affect emulsion stability to oil coalescence. At high pH, stable emulsions are formed due to the affinity of the particles to the interface. At low pH, protonation of the amine groups reduces the affinity and thus droplet coalescence is observed. Increasing the electrolyte concentration improves emulsion stability, but causes an increase in droplet size due to adsorption of flocculated/aggregated particles. Finally, it is shown that these latex particles can be used in conjunction with membrane emulsification techniques to produce emulsions with low polydispersity.